PHYSICAL CONDITIONING OF TEENAGERS IN DIFFERENT KIND OF SPORTS - Ciematnieks, Uģis; Streiķe, Beāte (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
Physical conditioning is crucial in building motion skills if the coach wants to ensure long-term athletic development. The essence is that physical conditioning needs to be developed before the development of technical skills of sports movements at a much higher intensity at each stage of the multi-annual training process. The adult competition system and training programs are being imposed on young athletes, so the essential motion skills are not being learned (Grāvītis @ Luika, 2015). The lack of physical conditioning in teenage years is very often reflected in the most inappropriate moments of an athlete's career, at the elite level. Insufficient physical conditioning is a reason for the instability of motion skills and injuries in extreme physical and psychological loads. The amount of physical activity can be measured as a step count. The aim of the research is to assess physical fitness rate for children practicing basketball, football or ice hockey with EUROFIT test battery. The study included boys, 100 basketball players, 100 soccer players and 100 ice hockey players from Latvia who were born in 2002 and started training in their sport during at the ages from 7 to 9, collected data of their conditioning for five years, divided into three age groups. According to EUROFIT tests, it was concluded that the ice hockey players have the highest physical conditioning rates according to EUROFIT standard from the athletes analyzed, and the basketball players have the lowest physical conditioning rates in EUROFIT tests from the athletes analyzed. We can conclude that the results of hockey players are higher than the scores of basketball and soccer players because ice hockey players practice more frequently, and dryland training is strictly organized, they develop all motor abilities that is needed for successive training in basic drills on ice.